2021
DOI: 10.4103/ijo.ijo_295_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the choroidal thickness and retinal nerve fiber layer and visual fields in morbid obesity

Abstract: Purpose: The study aimed to investigate the changes in choroidal thickness (CT), retinal nerve fiber layer thickness (RNFL), and visual field parameters in morbidly obese patients following bariatric surgery. Methods: The study included 40 morbidly obese patients with body mass indexes (BMI) ≥40 who had undergone bariatric surgery (Group 1) and 40 age-and sex-matched healthy subjects with normal BMI values (Group 2). RNFL and CT measurements by optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Obesity is a multisystemic disease, and it affects all tissues as well as the eye. The effects of obesity on ocular tissues have been reported in previous studies (7)(8)(9). Especially, the changes in the retina due to microvascular damage and inflammation may be observed.…”
Section: Introductionmentioning
confidence: 65%
“…Obesity is a multisystemic disease, and it affects all tissues as well as the eye. The effects of obesity on ocular tissues have been reported in previous studies (7)(8)(9). Especially, the changes in the retina due to microvascular damage and inflammation may be observed.…”
Section: Introductionmentioning
confidence: 65%
“…The relationship between the best CVA and the thicknesses was negatively correlated; as the P values were 0.78 and 0.58, respectively, the correlation was not obvious. Therefore, the role of nonvisual factors might affect the thickness of the RNFL, which was very inconsistent with the results of many foreign researches [ 31 ]. This may be influenced by racial differences or some subjective and objective factors, such as the degree of cooperation between patients, differences between individuals, and the size of the experiment sample.…”
Section: Discussionmentioning
confidence: 81%
“…Human retinal ganglion cells, retinal nerve fiber layer thickness, and choroidal thickness can all be significantly altered by obesity [ 220 , 221 , 222 ]. Several pieces of evidence showed that glaucomatous eyes have increased protein levels of proinflammatory cytokines, macrophage infiltration of the optic nerve [ 223 , 224 ], and intense inflammatory staining in the optic nerve head, which can damage the optic axon [ 225 , 226 ].…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%